Open Screw Placement in a 1.5 mm LCP Over a Fracture Gap Decreases Fatigue Life - Alwen, Sarah G. J.; Kapatkin, Amy S.; Garcia, Tanya C.; Milgram, Joshua; Stover, Susan M. (Frontiers in Veterinary Science, 2018)
Objective: To investigate the influence of plate and screw hole position on the stability of simulated radial fractures stabilized with a 1.5 mm condylar locking compression plate (LCP). Study Design: In vitro mechanical testing of paired cadaveric limbs. Sample Population: Paired radii (n=7) stabilized with a 1.5 mm condylar LCP with an open screw hole positioned either proximal to (PG), or over (OG), a simulated small fracture gap. Methods: Constructs were cycled in axial compression at a simulated trot load until failure or a maximum of 200,000 cycles. Specimens that sustained 200,000 cycles without failure were then loaded in axial compression in a single cycle to failure. Construct cyclic axial stiffness and gap strain, fatigue life, and residual strength were evaluated and compared between constructs using analysis of variance. Results: Of pairs that had a failure during cyclic loading, OG constructs survived fewer cycles (54,700 ± 60,600) than PG (116,800 ± 49,300). OG constructs had significantly lower initial stiffness throughout cyclic loading and higher gap strain range within the first 1000 cycles than PG constructs. Residual strength variables were not significantly different between constructs, however yield loads occurred at loads only marginally higher than approximated trot loads. Fatigue life decreased with increasing body weight. Conclusion: Fracture fixation stability is compromised by an open screw hole directly over a fracture gap compared to the open screw hole being buttressed by bone in the model studied. The 1.5 mm condylar LCP may be insufficient stabilization in dogs with appropriate radial geometry but high body weights.